TEACHING VOCABULARY USING FLASHCARDS AND WORD LIST: A Quasi-Experimental Study with Fifth Graders in One Public Elementary School in Binjai - Sitompul, Elsa Yusrika (2013)
This paper reports on a study concerned with teaching vocabulary using flashcards and word list to fifth graders in a public elementary school in Binjai. This study aimed to investigate whether flashcards or word list can help students' vocabulary mastery and to discover the students' responses toward both strategies in learning English vocabulary. This study employed a quasi-experimental research design which involved two classes, grouped into experimental and control groups with a relatively similar vocabulary mastery before treatment. This study also employed interview techniques to examine students' responses toward both strategies in learning vocabulary. The data were obtained from several weeks teaching phase in which the students were taught about vocabulary using flashcards in the experimental group and through word list in the control group. This study revealed that students' vocabulary mastery improved after they were taught by using flashcards and word list. However, students' vocabulary in experimental group increased more significantly than the control group. The result of the study suggests that flashcards are more effective in helping students master vocabulary. Moreover, students' responses toward the use of flashcards were positive. The students in experimental group admitted that they could: (1) memorize the words easily, (2) be more motivated to learn English, (3) understand vocabulary easily. On the other hand, students in the control group perceived that word list was a tedious strategy. It made them feel uninterested and pay less attention to learning vocabulary. Based on the findings, it is recommended that flashcards can be used in teaching English to young learners in other contexts. Abstrak ini melaporkan sebuah penelitian mengenai pengajaran vocabulary menggunakan flashcards dan word list di kelas 5 sebuah sekolah dasar di Binjai. Penelitian ini bertujuan untuk menyelidiki apakah flashcards atau word list dapat membantu penguasaan vocabulary siswa dan untuk mengetahui tanggapan siswa terhadap kedua strategi dalam mempelajari vocabulary bahasa Inggris. Penelitian ini menggunakan desain quasi eksperimental yang meliputi dua kelas yaitu kelas eksperimental dan kontrol. Kedua kelas tersebut relatif sama dalam penguasaan vocabulary sebelum dilakukannya treatment. Penelitian ini juga melakukan teknik interview untuk mengetahui tanggapan siswa terhadap kedua strategi dalam mempelajari vocabulary. Data diperoleh dari pengajaran di kelas setelah beberapa minggu dimana flashcards digunakan di kelas eksperimental dan word list di kelas kontrol. Penelitian ini mengungkapkan bahwa penguasaan vocabulary siswa meningkat setelah mereka diajarkan menggunakan flashcards dan word list. Tetapi siswa di kelas eksperimental meningkat lebih signifikan dibanding kelas kontrol. Hasil penelitian ini menyarankan flashcards lebih efektif dalam membantu siswa menguasai vocabulary. Selain itu, tanggapan siswa terhadap penggunaan flashcards positif. Siswa di kelas eksperimental mampu mengingat kata dengan mudah, lebih termotivasi belajar bahasa Inggris dan memahami vocabulary dengan mudah. Di samping itu, siswa di kelas kontrol merasa word list merupakan cara yang membosankan. Hal itu membuat mereka merasa tidak tertarik dan tidak fokus dalam mempelajari vocabulary. Berdasarkan hasil di atas, flashcards dapat digunakan dalam pengajaran bahasa Inggrs untuk anak-anak di konteks yang lain.